If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 = (180 + -1(2x + 60)) + (3x + 10) + x Reorder the terms: 180 = (180 + -1(60 + 2x)) + (3x + 10) + x 180 = (180 + (60 * -1 + 2x * -1)) + (3x + 10) + x 180 = (180 + (-60 + -2x)) + (3x + 10) + x Combine like terms: 180 + -60 = 120 180 = (120 + -2x) + (3x + 10) + x Remove parenthesis around (120 + -2x) 180 = 120 + -2x + (3x + 10) + x Reorder the terms: 180 = 120 + -2x + (10 + 3x) + x Remove parenthesis around (10 + 3x) 180 = 120 + -2x + 10 + 3x + x Reorder the terms: 180 = 120 + 10 + -2x + 3x + x Combine like terms: 120 + 10 = 130 180 = 130 + -2x + 3x + x Combine like terms: -2x + 3x = 1x 180 = 130 + 1x + x Combine like terms: 1x + x = 2x 180 = 130 + 2x Solving 180 = 130 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 180 + -2x = 130 + 2x + -2x Combine like terms: 2x + -2x = 0 180 + -2x = 130 + 0 180 + -2x = 130 Add '-180' to each side of the equation. 180 + -180 + -2x = 130 + -180 Combine like terms: 180 + -180 = 0 0 + -2x = 130 + -180 -2x = 130 + -180 Combine like terms: 130 + -180 = -50 -2x = -50 Divide each side by '-2'. x = 25 Simplifying x = 25
| y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 | | 7(x-2)+2(x+1)=1-3x | | 11x-2y=18 | | (12x+3x+2)-(12x+5)=6x+11 | | 2(3*5)=6y | | x-3x+2x=-310 | | 2x^6-9x^5+10x^4-3x^3+10x^2+2=0 | | 7x+35=77 | | (8x*2+5x+4)-(8x*2+5)=8x+10 | | 180=-10-120+x-3x+2x | | (5x*2+6x-1)-(5x*2+8)=15 | | 310=-2x+2x | | x-.1x=231 | | 180=x-(3x+10)-(180-(2x+60)) | | 5c^2-2-9c= | | 11/14=18/x |